已知\( {y^{(4)}} = {x^2} + 2x \),则\( {y^{(5)}} = 2x + 2 \)( ).
举一反三
- 已知\( y = {x^2} + 2x \),则\( y' \)为( ). A: \( 2x + 2 \) B: \( 2x \) C: \( 0 \) D: \( x \)
- 已知\( y = {e^{2x}} \),则\( y' \)为( ). A: \( {e^x} \) B: \( 2{e^x} \) C: \( {e^{2x}} \) D: \( 2{e^{2x}} \)
- 已知\( y = {x^3}\cos 2x \),则\( y'' \)为( ). A: 0 B: \( 6x\cos 2x{\rm{ + }}12{x^2}\sin 2x - 4{x^3}\cos 2x \) C: \( 6x\cos 2x - 12{x^2}\sin 2x{\rm{ + }}4{x^3}\cos 2x \) D: \( 6x\cos 2x - 12{x^2}\sin 2x - 4{x^3}\cos 2x \)
- 设 $y=\tan x^2$,则 $y'=$( ). A: $\sec x^2$ B: $\sec^2 x^2$ C: $2x\sec^2 x$ D: $2x\sec^2 x^2$
- 函数\(y = \sin{x^2}\)的导数为( ). A: \( - 2x\sec {x^4}\) B: \(2x\cos {x^2}\) C: \(2x\sec {x^2}\) D: \(- 2x\sec {x^2}\)